Development of Emotional and Volitional Resilience of Future Officers of Defense and Security Sector of Ukraine During Professional Training - Balendr, Andrii; Komarnytska, Oksana (Educological discourse, 2023)
The article highlights the specifics of emotional and volitional resilience development of future officers of the defense and security sector of Ukraine during professional training at the higher military educational institutions (HMEI). The emotional and volitional resilience of future officers of the defense and security sector of Ukraine is considered as a holistic characteristic of the mental component of their purposeful managerial activity in everyday and, especially, extreme and combat conditions, readiness to resist the stressogenic influence of stress factors of adverse situations of military-professional activity. The emotional and volitional resilience includes a systematic practical ability to withstand extreme excitement and emotional stress under the influence of military service stressors, in particular, stress factors of the combat situation. Stimulation of emotional and volitional resilience of future officers should include exercises and techniques modified in accordance with the purpose and objectives of the training program at the HMEI for the formation and development of cadets’ resilience. The specified professional training should be filled with necessary, practically oriented psychological knowledge and enrich the entire educational process with not only methods to form emotional and volitional resilience, but also create conditions for the internal growth of the cadets’ personality. Thus, training program for the formation and development of emotional and volitional stability of cadets should be an important addition to the system of psychological training that functions at the HMEI of the security and defense sector Ukraine.